Exploration of the Effects of Different Beauveria bassiana Strains on Dioryctria sylvestrella Larvae from the Perspective of Oxidative Stress - Ruting Chen; Meiling Wang; Hanwen Zhang; Jianjiao Xu; Xiaomei Wang; Defu Chi; Jia Yu (Insects, 2025)
(1) Background: The larvae of Dioryctria sylvestrella typically bore into the shoots and cones of Pinus koraiensis, increasing tree breakage risk and reducing cone yield. (2) Methods: Five Beauveria bassiana strains were evaluated for virulence against fourth-instar larvae. And the levels of T-AOC and MDA in the larvae infected by each strain were measured. To assess larval responses to different strains, we measured the activities of six enzymes (SOD, CAT, POD, PPO, CarE, GST) and the levels of GSH and H2O2 in larvae treated with each strain. Additionally, the infection process of highly pathogenic B. bassiana in larvae was explored using scanning electron microscopy (SEM). (3) Results: Strain CGMCC3.2055 demonstrated the highest toxicity to larvae, achieving a cumulative corrected mortality of 80.56% on the 4th day and an LT50 of 3.248 days. The T-AOC of larvae treated with strain CGMCC3.2055 was inhibited within 48 h. The relative MDA content in this group was significantly higher than that in other strain-treated groups at 6, 12, and 24 h. In Bb01-treated larvae, H2O2 accumulation at 6 and 24 h post-infection was influenced by POD activity rather than GSH levels; in BbZ1-treated larvae, the activities of CAT and POD were upregulated at 6 and 36 h, while the activity of SOD was downregulated, but the content of H2O2 increased significantly, resulting in accumulation; in CFCC81428-treated larvae, a decline in T-AOC coincided with substantial H2O2 accumulation over 48 h, while a concomitant increase in GSH content bolstered tolerance to lethal oxidative damage; in CGMCC3.2055-treated larvae, H2O2 only accumulated significantly at 24 and 48 h, yet upregulated CAT and POD were insufficient to effectively scavenge the excess H2O2; and in bio-21738-treated larvae, SOD-driven dismutation generated substantial H2O2 from 12 to 48 h, leading to pronounced accumulation from 6 to 48 h, yet limited upregulation of POD (only at 6 and 12 h) and CAT (only at 12 and 48 h) were insufficient to mitigate H2O2 buildup. PPO activity was upregulated within 48 h in all treatment groups except for BbZ1, where no upregulation was observed at 12 and 48 h. GST activity was upregulated in all treatment groups except for CGMCC3.2055, where a downregulation was observed at 12 h post-infection. CarE activity was significantly upregulated within 48 h in both CFCC81428 and CGMCC3.2055 groups; in the Bb01 group, CarE was upregulated only at 6 and 48 h; in the BbZ1 group, CarE was downregulated only at 48 h; and in the bio-21738 group, CarE showed no upregulation at 24 and 48 h. Through SEM, the infection process of the strain CGMCC3.2055 on the surface of the larvae was further determined, which mainly included adhesion, the appearance of bud-like protrusions, the growth of germ tubes along the epidermis and penetration of the epidermis, as well as the colonization of the strain and its emergence from the surface of the larvae. (4) Conclusions: This study first screened the highly pathogenic B. bassiana strain CGMCC3.2055 by evaluating its virulence to larvae and post-infection T-AOC and MDA levels. It also clarified the strain’s infection process and the larvae’s immune responses to various strains.